FAKTOR- FAKTOR YANG MEMPENGARUHI MOTIVASI WANITA BEKERJA SEBAGAI BURUH PABRIK GARMEN DI PT AMEYA LIVING STYLE INDONESIA - Wantini .; Kurniati . (JESI (Jurnal Ekonomi Syariah Indonesia), 2013)
Abstract This study aims to identify how the effect of economic motives and religious motives that influence the motivation of women to work as a garment factory worker. Penganbilan in this study used a sample of 50 respondents, data collection techniques with the use of questionnaires, and research variables are economic motives (X1), religious motives (X2), and the motivation of women to work as factory worker (Y). Data validity was tested using the Pearson product moment correlation, and to mengujitingkat Cronbach alpha reliability using, then the data is processed by Multiple Linear Regression Analysis. Hypothesis testing using t test and F test with a significance level of 5%. This research uses tools SPSS version 13. These results indicate that there is significant influence of each variable on the motivation of women to work as factory workers. Keywords: Women, motivation, worker